2016
DOI: 10.1364/boe.7.004400
|View full text |Cite
|
Sign up to set email alerts
|

Extended-focus optical coherence microscopy for high-resolution imaging of the murine brain

Abstract: We propose a new method and optical instrumentation for mouse brain imaging based on extended-focus optical coherence microscopy. This in vivo imaging technique allows the evaluation of the cytoarchitecture at cellular level and the circulation system dynamics in three dimensions. This minimally invasive and non-contact approach is performed without the application of contrasting agents. The optical design achieved a resolution of 2.2 μm over a distance of 800 μm, which was sufficient to obtain a detailed thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…At the focal plane, our xf‐OCM had ∼5 dB lower SNR and ∼10 dB higher sidelobe than standard OCM. Although its performance of focus extension was not as good as previous axicon‐based xf‐OCM systems , it gained advantanges of smaller SNR loss and sidelobes, as well as the ease of integrating an annular mask into the imaging system. Our study also showed that this xf‐OCM system was immune to spherical aberrations caused by mismatched refractive indexes of different mediums in the light path.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…At the focal plane, our xf‐OCM had ∼5 dB lower SNR and ∼10 dB higher sidelobe than standard OCM. Although its performance of focus extension was not as good as previous axicon‐based xf‐OCM systems , it gained advantanges of smaller SNR loss and sidelobes, as well as the ease of integrating an annular mask into the imaging system. Our study also showed that this xf‐OCM system was immune to spherical aberrations caused by mismatched refractive indexes of different mediums in the light path.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, the imaging speed was reduced, which may not be desired in time‐sensitive imaging experiments, such as detecting the blood flow with a phase variance OCM technique . However, in cases of the light source being ultrafast lasers, such as femtosecond lasers, the annular mask is no longer an issue for energy efficiency since these laser sources usually have a broad range of high output power levels . We can easily compensate the loss of light power, caused by the annular mask, through raising the laser power.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Bessel beam with a spot size similar to a Gaussian beam offers a longer depth of focus [71][72][73]. The compromise here is that Bessel beams have relatively strong side lobes which can affect the accuracy of some OCT measurements.…”
Section: Objective Lensmentioning
confidence: 99%